Guia de práticas relevantes na implementação de infraestrutura de cloud computing em startups tecnológicas - Petrili, Breno Ribeiro (2023)
The world has gone through major transformations with technological evolution and globalization, making technology delivery speed in companies to grow exponentially, due to new products and services demands. This reality let emerge a new company’s segment called startup, which represents an effort to create a new business model. Startups depend on Information Technology that must be used in a scalable, fast and reliable way to support new business activities. On the other hand, cloud computing, a service provided by providers who deliver technology infrastructure on demand, is a potential ally for the Startups success. However, due to business characteristics, technology startups, according to the researched literature, lack a set of guides or a set of practices that would be relevant in cloud computing infrastructure Implementation. In this context, this research objective is to develop and validate a Relevant practices guide in cloud computing infrastructure implementing in technological startups, from architecture, performance, elasticity, security and costs the perspective, identifying and characterizing needs involved in a technology startup infrastructure construction. The study is developed in qualitative and exploratory approach, using systematic review of literature, face test and field research. The practices relevance obtained in literature has been validated by solid experienced cloud computing experts in brazilian startup market. As academic work results, a relevant practices guide in cloud computing infrastructure implementing in technological startups has been developed, consisting of 56 practices categorized in 5 dimensions – “Architecture”, “Performance”, “Elasticity”, “Security” and “Costs” – and sub-categorized in 6 guidelines – “Strategy”, “Plan”, “Ready”, “Adoption”, “Govern”, and “Manage and Operation”. As a guide contribution, it is expected to enable Startups to explore opportunities that Cloud Computing offers, as well as knowledge dissemination needed for emerging and establishing new solid and scalable technological startups.